(untitled) (INTERNATIONAL CONFERENCE ON INTERDISCIPLINARY SCIENCE, 2025)
This article analyzes the theoretical and practical aspects of using modern pedagogical technologies in developing speech culture of primary school students through teaching the mother tongue. The study explores the possibilities of forming oral and written speech based on interactive methods, information and communication technologies, learner-centered and competency-based approaches. The effectiveness of modern pedagogical technologies in improving speech culture of primary school students is scientifically substantiated.